FRI0521 MIRNA-150 AS A NOVEL REGULATOR OF POST-TRAUMATIC OSTEOARTHRITIS. (June 2019) - Adlaan, Asaad Al; Cook, Bryson; Jaber, Fatima; Safadi, Fayez
Abstract : Background: Osteoarthritis (OA) is a chronic joint disease causes irreversible damage to the articular cartilage resulting in loss of joint function and subchondral bone remodeling. There is no cure for OA and currently the available treatment like pain management, and joint replacement surgery is used to treat this disease. MiRNAs are small non-coding RNAs consist of 21-29 nucleotides which regulate gene expression by targeting the 3' untranslated region (UTR) leading to translation inhibition. In recent years, many studies showed that microRNAs could be a target for many diseases including OA. Our preliminary data on osteoactivin showed that the GPNMB acts as a protective protein in osteoarthritis by reducing catabolic gene expression. Our lab group results have been shown that miRNA-150 targets the 3'UTR of osteoactivin in osteoblast cells. Objectives: There is no study regarding the role of miRNA 150 on cartilage homeostasis and because the miRNA 150 targets osteoactivin in lung and bone cells, we hypothesized that miRNA-150 targets osteoactivin in chondrocytes and protect cartilage ECM degradation. Methods: RNAs were isolated from primary chondrocytes of miRNA- 150 knockout pups, then was used in qPCR to measure gene expression. Western blot used to detect MMP-3, MMP-9, MMP-13, IL-6, collagen type-II and aggrecan. In addition, histological analysis was used to test the role of miRNA-150 vivo through evaluating proteoglycan degradation by toluidine blue staining and immunohistochemistry after 12 weeks from DMM surgery. PCR transcription factors and signaling pathway finder array were used to elucidate the altered genes and transcriptions factors compared to the wild type in primary chondrocytes culture. Results: Primary chondrocytes from 150 KO mice showed high mRNA expression levels of GPNMB compared to the wild type mice. Medial tibia plateau (MTP) and medial femur condyle (MFC) have been graded by OARSI scoring system after 12 weeks of DMM surgery. Histological results showed that the 150 KO mice have less cartilage damaged compared to the wild type. To determine whether epigenetic modifiers (miRNAs) regulating GPNMB/Osteoactivin expression can modulate the cartilage protective effects of GPNMB/Osteoactivin, we found that miRNA 150 targets GPNMB/Osteoactivin in chondrocytes. Next, we examined the effects of miRNA 150 deficiency on the OA progression in vivo and found that miRNA 150 KO are more protected against post-traumatic OA compared to WT mice. Furthermore, we assessed the expression of GPNMB/Osteoactivin in miRNA 150 KO chondrocytes and showed a significant increase compared to WT cells. Conclusion: These results showed that miRNA is negative regulator of cartilage homeostasis and blocking miRNA might have therapeutic potential fort he treatment of age-related osteoarthritis and post-traumatic induced osteoarthritis. References: The surgical destabilization of the medial meniscus (DMM) model of osteoarthritis in the 129/SvEv mouse. Methods in Molecular Biology: Osteoporosis and Osteoarthritis. Loeser RF, Goldring SR, Scanzello CR, Goldring MB. Osteoarthritis: A disease of the joint as an organ. Arthritis and Rheumatism. 2012. pp. 1697–1707. [1] Zhou, L., Zhuo, H., Ouyang, H., Liu, Y., Yuan, F., Sun, L., . .. & Liu, H. (2017). Glycoprotein non-metastatic melanoma protein b (Gpnmb) is highly expressed in macrophages of acute injured kidney and promotes M2 macrophages polarization. Cellular immunology, 316, 53-60. [2] Ripoll, V.M., et al., Gpnmb is induced in macrophages by IFN-gamma and lipopolysaccharide and acts as a feedback regulator of proinflammatory responses. J Immunol, 2007. 178(10): p.655766. Acknowledgement: This research was funded by the Cook Research Fund and Ohio Department of Education. Disclosure of Interests: None declared